Analisis Hubungan antara Rasio Harga Saham terhadap Nilai Buku Perusahaan dan Imbal Hasil Saham sebagai Dasar Penentuan Strategi Investasi - Pandowo, A. Widodo (Jurnal Widya Manajemen & Akuntansi, 2002)
The general objective of this study is to analyze the relationship between price book value ratio and stock return as basic decision of strategic investment in BEJ The samples for this study consisted of 57 out of 146 manufacturing company listed in BEJ. To achieve this objective, 57 manufacturing company meeting the criteria have taken : companies have positive ROE and PBV. The result of this study performs that price book value ratio can be used to make basic decision of strategic investment, also to predict stocks price (undervalued or overvalued).